A comparison of dacron versus flocked nylon swabs for anal cytology specimen collection - Gage, Julia C.; Ghosh, Arpita; Borgonovo, Sylvia; Follansbee, Stephen; Wentzensen, Nicolas; Gravitt, Patti E.; Grabe, Niels; Lahrmann, Bernd; Castle, Philip E. (Acta cytologica, 2011)
Objectives: We compared the performance of commonly used Dacron versus flocked nylon swabs for anal cytology. Study Design: From 23 HIV-positive men screened at Kaiser Permanente San Francisco (San Francisco, Calif., USA), 2 anal specimens were collected, 1 with each swab in random order, and placed into liquid cytology medium. Specimens were tested for cellularity by quantifying a genomic DNA (erv-3). The number of cells was assessed from prepared slides by automated image analysis. Performance was compared between swabs using 2-sample t tests and standard crossover trial analysis methods accounting for period effect. Results: Flocked swabs collected slightly more erv-3 cells than Dacron for the first sample although not significantly (p = 0.18) and a similar number of erv-3 cells for the second sample (p = 0.85). Flocked swabs collected slightly more cells per slide than the Dacron swabs at both time periods although this was only significant in the second time period (p = 0.42 and 0.03 for first and second periods, respectively). In crossover trial analysis, flocked swabs outperformed Dacron for cell count per slide based on slide imaging (p = 0.03), but Dacron and flocked swabs performed similarly based on erv-3 quantification (p = 0.14). Conclusions: Further studies should determine whether flocked swabs increase the representation of diagnostically important cells compared to Dacron.
Gesehen am 06.07.2023